EMBRIOGENESIS SOMATIK UBI KAYU (Manihot esculenta CRANTZ.) KLON WAXY PADA BEBERAPA JENIS DAN KONSENTRASI AUKSIN 2,4-D ATAU PICLORAM DAN NAA - Erlangga, Wahyu; Yelli, Fitri; Yusnita, Yusnita; Utomo, Setyo Dwi (Universitas Lampung, 2025)
Indonesia is one of the largest cassava producing countries in the world with various types and advantages. Waxy clones have a high starch content and therefore they can be used as a food substitute for rice. Tissue culture through somatic embryogenesis is an effective technique for rapid and mass seedling propagation. This research aimed to determine the effect of the type and concentration of auxin 2,4-D or picloram and the addition of NAA on the formation of Waxy cassava clone somatic embryos. This research used a completely randomized design (CRD) which was arranged in a non-factorial. Auxin 2,4-D and picloram were used at four concentration levels: 0 mg.l-1, 8 mg.l-1, 10 mg.l-1, 12 mg.l-1, and additional NAA treatment of 6 mg.l-1 each. Results showed that MS + 6 mg.l-1 NAA treatment produced the highest callus weight. Meanwhile, the percentage of embryonic callus and number of embryo was higher in the treatment of MS + picloram 12 mg.l-1 and NAA 6 mg.l-1 (19,05 ± 5,82 %) and MS + 8 mg.l-1 2,4-D + 6 mg.l-1 NAA (11,11 ± 3,17 %) with 5,48 ± 3,56 and 4,93 ± 1,95 embryos, respectively. Thus, auxin picloram 12 mg.l-1 + NAA 6 mg.l-1 were the most effective in inducing the formation of somatic embryos on waxy cassava clone.